Emerging multi-drug resistant and extended-spectrum β-lactamase (ESBL)-positive enterotoxigenic E. coli (ETEC) clones circulating in aquatic environments and in patients - Enrique Joffré; Alberto J. Martín-Rodríguez; Annie Justh de Neczpal; Astrid von Mentzer; Åsa Sjöling (One Health)
Diarrheal disease pathogens often spread through water-borne routes. Enterotoxigenic Escherichia coli (ETEC) is a major bacterial agent causing diarrheal disease in children, adults, and travelers in endemic areas. In addition, ETEC is responsible for outbreaks of water and food-borne gasteroenteritis globally, ETEC isolates also show robust survival capacity in various environmental settings, including aquatic environments.During the last decade, studies of ETEC isolates have indicated a rapid increase in multi-drug resistant and extended-spectrum β-lactamase (ESBL)-positive human-specific ETEC strains. These have been found in both environmental water sources and human patients, warranting the urgent need for focused monitoring of antibiotic resistance development in ETEC.Whole genome sequencing (WGS) of isolates from environmental, animal, and human sources enables in silico surveillance of emerging pathogenic and multi-drug resistant strains. This method allows for re-analysis of genomic data, aiding in identification of new variants of pathogenic clones.By integrating data from diverse sources inclusing sequenced isolates, we found that certain ETEC clonal lineages e.g., those expressing certain toxin-colonization factor profiles including STp/CS6, LT STh/CS2 + CS3, and LT STh/CFA/I are more at risk to develop multi-drug resistance than other ETEC lineages. Comparizon of multi-locus sequence types from papers with WGS data indicated ST182, ST4, ST2332 and new ST types to be emerging multi-drug resistant ETEC.We conclude that further studies on sequenced ETEC/E. coli genomes are needed to enhance our understanding of the dynamics of ETEC evolution, and the relation of virulence and resistance profiles in both environmental and clinical isolates.